Gender Differences in Work Motivation of Public Basic Education in Metro Vigan and Caoayan, Philippines and Job Satisfaction - Magallanes, Theogenia; Abun, Damianus; Mansueto, Jacel; Flores, Nathanael (International Journal of English Literature and Social Sciences (IJELS), 2019)
The study wanted to determine the differences in work motivation and job satisfaction of male and female teachers and to determine the relationship between work motivation and job satisfaction. To carry out such purpose, related literatures and studies were reviewed to support the theory of the study and proper methodology was followed. The study used descriptive correlational method of research design and aided by fact finding inquiry. The population of the study were 263 teachers. of basic public schools of Metro Vigan and Caoayan. Validated Questionnaires were used to gather the data and to treat the data statistically, mean, t-test and Pearson r were used. Mean was to measure the level of motivation and job satisfaction and t-test was used to measure the difference and Pearson r was used to determine the correlation. The study found that work motivation and job satisfaction of basic public schools in Metro Vigan and Caoayan is very high and there was no correlation between work motivation of both gender and job satisfaction. It also found that there was no difference between job satisfaction of male and female teachers and as whole, there was no difference between work motivation of both genders but taking it singly, there was a difference on work motivation of both genders in terms of integrated regulation.